Peculiarities in the orthopaedic provision of patients having foot deformities with inserted orthopaedic products - Yaremenko, Dmytro; Korolkov, Oleksandr; Kikosh, Gennadiy; Kuznetsov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
On the basis of the results of an extensive clinical-radiological and podometric examination of 864 children and adults with the most common foot deformities (flat valgus, broad foot and hollow varus), indications and peculiarities of their orthopaedic provision were determined. Also, design features and parameters of corrective elements of orthopaedic insoles and footwear were grounded. An opportune use of corrective insoles and rational footwear in the therapeutic process normalized axial relationships in both the foot and the “foot - lower extremity - pelvis - vertebral column” system, thereby creating necessary conditions for the development of the foot and above-located segments of the locomotor system in the natural, anatomically and functionally advantageous position, and ensuring the harmonious physical development of the patient.